Development of a Job-Exposure Matrix for Assessment of Occupational Exposure to High-Frequency Electromagnetic Fields (3 kHz–300 GHz). Issue 9 (7th September 2019) - Migault, Lucile; Bowman, Joseph D; Kromhout, Hans; Figuerola, Jordi; Baldi, Isabelle; Bouvier, Ghislaine; Turner, Michelle C; Cardis, Elisabeth; Vila, Javier
Abstract: Objectives: The aim of this work was to build a job-exposure matrix (JEM) using an international coding system and covering the non-thermal intermediate frequency (IF) (3–100 kHz, named IFELF), thermal IF (100 kHz–10 MHz, named IFRF), and radiofrequency (RF) (>10 MHz) bands. Methods: Detailed occupational data were collected in a large population-based case–control study, INTEROCC, with occupations coded into the International Standard Classification of Occupations system 1988 (ISCO88). The subjects' occupational source-based ancillary information was combined with an existing source-exposure matrix and the reference levels of the International Commission on Non-Ionizing Radiation Protection (ICNIRP) for occupational exposure to calculate estimates of level (L) of exposure to electric (E) and magnetic (H) fields by ISCO88 code and frequency band as ICNIRP ratios (IFELF) or squared ratios (IFRF and RF). Estimates of exposure probability ( P ) were obtained by dividing the number of exposed subjects by the total number of subjects available per job title. Results: With 36 011 job histories collected, 468 ISCO88 (four-digit) codes were included in the JEM, of which 62.4% are exposed to RF, IFRF, and/or IFELF. As a reference, P values for RF E-fields ranged from 0.3 to 65.0% with a median of 5.1%. L values for RF E-fields (ICNIRP squared ratio) ranged from 6.94 × 10 −11 to 33.97 with a median of 0.61. Conclusions: The methodology used allowed the development of a JEM for high-frequency electromagnetic fields containing exposure estimates for the largest number of occupations to date. Although the validity of this JEM is limited by the small number of available observations for some codes, this JEM may be useful for epidemiological studies and occupational health management programs assessing high-frequency electromagnetic field exposure in occupational settings.